2012
DOI: 10.1016/j.ydbio.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin-2b regulates endocardial morphogenesis in zebrafish

Abstract: scotch tape (sco) is a zebrafish cardiac mutant initially proposed to exhibit a reduced amount of cardiac jelly, the extracellular matrix between the myocardial and endocardial layers. We analyzed sco(te382) mutant hearts in detail using both selective plane illumination microscopy (SPIM) and transmission electron microscopy (TEM), and observed a fascinating endocardial defect. Time-lapse SPIM imaging of wild-type and mutant embryos revealed significant and dynamic gaps between endocardial cells during develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
(55 reference statements)
2
17
0
1
Order By: Relevance
“…S3G). Consistent with the previous report (Mellman et al, 2012), we found that fbn2bMO morphants lost most of the Tg(kdrl:EGFP) atrial endocardium but had no defect in the Fig. 3.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…S3G). Consistent with the previous report (Mellman et al, 2012), we found that fbn2bMO morphants lost most of the Tg(kdrl:EGFP) atrial endocardium but had no defect in the Fig. 3.…”
Section: Resultssupporting
confidence: 92%
“…nonsense mutation in sco te382 mutants, phenocopying sco te382 mutant phenotypes by antisense pku300 morpholino knockdown, rescuing sco te382 mutant phenotypes by overexpressing the wildtype pku300 gene in the endothelium and endocardium, and determining pku300 mRNA expression in the endocardium. As reported recently (Mellman et al, 2012), we also found the G3935T missense mutation of fbn2b in our sco te382 mutant. Mutational analyses of fbn2b and pku300 allowed us to further classify two groups of mutants in sco te382 , where group I mutants were heterozygous for both genes and group II mutants were homozygous for both genes (supplementary material Table S2; Fig.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations